The Rhetorical Structure and Research Gap Strategies of Journal Article Abstracts in Language-Related Fields Published in High-impact International Journals - Arsyad, Safnil; Madani; Pratiwi, Vika Armanda; An-Nashir, Abdullah Azzam; Erviona, Lussy; Hasiyanti; Marjelina, Oktasya (LEARN Journal: Language Education and Acquisition Research Network, 2023)
Authors should attract readers to read their articles from the very beginning of the article; this is important because readers will stop reading an article if they are not sure that they will obtain new, interesting and important information from the article. This study aims to investigate the rhetorical moves found in a research article abstract (henceforth RAA) published in high-impact international journals and how authors employ a research gap strategy (henceforth RGS) in their article abstracts. One hundred abstracts were chosen from ten high-impact international journals in language-related fields (henceforth LRF) for this study. The results showed that the RAAs have at least 4 moves (Moves 2, 3, 4, and 5) while only 55 or 55% of them have an RGS in the abstracts. The most frequent RGS used by the authors was Strategy 2 and the least employed strategies were Strategy 1 and Strategy 4. This implies that, although publishing in high-impact international journals, authors in LRF tend not to use Strategy 1 (nonexistence or absence of research on a particular topic or aspect) and Strategy 4 (contrasting or conflicting previous research ﬁndings) in their RAAs but they may address these strategies in their article introductions.